Pengembangan teknologi berbasis media air subkritis dan CO2 bertekanan untuk intensifikasi proses - Firman Kurniawansyah (Jurnal Rekayasa Proses, 2019)
Green solvent, an environmentally friendly solvent in form of subcritical water (SBCW) and pressurized CO2, has been used as media in process intensification. It has characteristic of having low or even zero toxicity. Hence it can simplify purification procedure. In this communication, development of technology applications of those green solvents, i.e. extraction, particle synthesis, and reaction engineering, is briefly presented. In general, studies show a positive utilization of green solvents of subcritical water and pressurized CO2. For example, in pectin extraction, yield up to 90% has been obtained when the combined solvent was used. In another application, hydrolysis using SBCW-CO2 as combined solvent has facilitated 100% conversion of pinene.